1996
DOI: 10.1152/jappl.1996.81.1.355
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic growth factor mRNA responses in muscle to a single bout of exercise

Abstract: A major adaptation to exercise is new capillary formation in skeletal muscle. On the basis of angiogenesis in tumors and during development, several angiogenic growth factors may be involved, including vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), and transforming growth factor-beta 1 (TGF-beta 1). In 9-wk-old female Wistar rats, mRNA expression for these three growth factors in gastrocnemius muscle was examined by quantitative Northern analysis after a single 1-h run at 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
284
6
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(316 citation statements)
references
References 0 publications
22
284
6
4
Order By: Relevance
“…The VEGF mRNA response to increases in exercise intensity has been shown previously. 7,8 Exercise is essential to accelerate neovascularization and thereby elicit a healing response in the injured tendon. Increased levels of angiogenic growth factors, such as VEGF, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF mRNA response to increases in exercise intensity has been shown previously. 7,8 Exercise is essential to accelerate neovascularization and thereby elicit a healing response in the injured tendon. Increased levels of angiogenic growth factors, such as VEGF, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in capillary supply preceding the changes in oxidative enzymes were described previously (Pette et al 1973;Brown et al 1976), and were confirmed more recently (Skorjanc et al 1998) using different stimulation regimes than those used in the present study. It is normally assumed that increased activity of oxidative enzymes in muscles of endurance-trained animals is a sign of hypoxia which triggers capillary growth, possibly via vascular endothelial growth factor (VEGF; Breen et al 1996). This hypothesis would seemingly be supported by previous experiments showing that, when all fibres were stimulated for 2 days, capillary density was higher than in control muscles in the vicinity of fast glycolytic fibres while there was, at this early stage, no change in the capillary supply in the vicinity of the highly oxidative fibres (Hudlick a et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a single, 1-h bout of exercise of normal skeletal muscles increases the messenger ribonucleic acid (mRNA) levels of VEGF, bFGF and TGF-b 1 [9] (more so in hypoxia for VEGF, in particular). In addition, electrical stimulation increases VEGF levels [10].…”
mentioning
confidence: 99%